The effects of N-heterocyclic ligands on the nature of the Ru–(NO) bond in ruthenium tetraammine nitrosyl complexes - Caramori, Giovanni F. (Array, 2009)
Summary: Quantum chemical calculations at the DFT level have been carried out to analyze quantitatively the RuII–(NO)+, RuIII–(NO)0 and RuII–(NO)0 bonds in trans-[RuII(NH3)4(L)(NO)]q and trans-[RuII(NH3)4(L)(NO)]q−1 complexes, where L = 4-picoline (4-pic), C-bound imidazole (imC), N-bound imidazole (imN), nicotinamide (nic), pyridine (py), and pyrazine (pz). Equilibrium geometries and the vibrational frequencies are reported for the ground state GS and light-induced metastable states, MS1 and MS2, presenting good agreement with the experimental data. The nature of the RuII–(NO)+ and RuII–(NO)0 bonds was investigated by means of the energy decomposition analysis, EDA. The Ru–(NO) bonding situation has been analyzed in two different situations: prior and after one-electron reduction at the NO+ group. The EDA results for the complexes prior to the reduction of the NO+ indicate that the metalligand π-orbital interactions between NO+ and the [RuII(NH3)4(L)]q−1 are the most important term and that the trans-ligands imN and nic contribute to an increase in the π-donor strength of the metal centre towards NO+. For RuIII–(NO)0 bonds, the smallest values of ΔEint, ΔEPauli, ΔEelstat, and De are observed when L = imC or L = nic, independent of the state under consideration, GS or MS1, indicating that when L = imC or nic the RuIII–(NO)0 bond in GS or in MS1 states is more labile. After the reduction of the NO+ group, the RuII–(NO)0 becomes more labile when the trans-ligand is imC, which agrees with the experimental rate constants of NO0 dissociation